Implementing Human-Centric Design in Developing a Multifunctional Chair and Storage Solution for Children - Dangkua, Naufal Yunaz; Nandito, Muhammad Arya; Jamil, Farhana Haifa Putri; Rahayu, Mira (Jurnal Sistem Teknik Industri, 2024)
This research applies Human-Centric Design (HCD) principles to develop a multifunctional storage solution integrated with a chair, specifically designed for children. By considering the needs and preferences of both parents and young users, we combine ergonomic design elements with practical storage functionality. The resulting product not only organizes children’s belongings for parents but also provides an enjoyable experience for kids. Our study contributes to a deeper understanding of how HCD can effectively create functional and appealing products for parents and child users.